Padrões e processos associados à diversidade da anurofauna em áreas abertas da América do Sul: filogeografia de physalaemus cuvieri (anura: leptodactylidae) - Miranda, Núbia Esther de Oliveira (2014)
Phylogeographic studies are revealing complex evolutionary histories in the South American diagonal of open formations. The phylogeographic patterns of South American biota are better documented for forest-dwelling species but remain insufficient in respect to open vegetation habitats. The frog Physalaemus cuvieri presents wide distribution being a typical species of open areas. It represents an ideal model to investigate hypotheses about the role of events of Tertiary versus Quaternary in the genetic diversity and diversification of the anurofauna of the Neotropical open areas. Here we used a range-wide sampling of P. cuvieri and DNA regions with different mutation rates to investigate historical and spatial process that promoted the species diversification. We integrated the phylogeographic approach with ecological niche models to understand how Miocene/Pliocene orogenic events and/or Pleistocene climatic oscillations have contributed to shape the current diversity and distribution of the species population. We sampled 609 individuals from 76 populations. Three mitochondrial fragments (12S, 16S and cytochrome b) and one nuclear (rhodopsin) were sequenced for all individuals. We identified 248 haplotypes in mitochondrial region and six haplotypes in nuclear region. It is possible to recognize three haplogroups, widely distributed in the network, which assemble sympatric and geographically close populations haplotypes. There is a clear separation between the haplotypes that shows a ‘diagonal break’ of the populations of P. cuvieri with their connnection occurring in the northeast through the haplotypes of São Luiz - MA population. The hierarchical AMOVA showed significant differentiation among populations of the different river basins (FCT = 0.273). The divergence between the lineages of P. cuvieri and outgroups occurred during the Miocene, around 16.13 Ma [SD 10.43 to 20.43]. Divergences between the major groups and subgroups occurred during the Miocene (between 16 and 5.7 Ma). Divergences in the Pleistocene occurred mainly within populations, or among geographically close populations. The analysis of spatial diffusion estimated the most recent dates for the dispersal events of the lineages of P. cuvieri. Much of their diversification remained registered in the Tertiary, although we can not neglect the influence of Quaternary climatic fluctuations. Lineages of P. cuvieri seems to have an origin at central Brazil, with three main routes of colonization: one towards the south, one to the north and other to the northwest. The potential distribution of P. cuvieri appears did not change drastically across the last glacial cycle. Our results revealed a complex history diversification of P. cuvieri, with Tertiary orogenic events playing prominent role in the early diversification, by also favored by the climatic fluctuations of the Quaternary. This process contributed to the diversification of younger lineages and also structured populations. Therefore, P. cuvieri shows a pattern of deep divergences with strong regional structuring of populations, despite its widespread distribution and generalized ecology. Because of that deep and structured divergence, Physalaemus cuvieri populations also should be treated as a species complex